Islamic Sexual Education: Necessity for Imparting Sexual Modesty - Abdul Fatai Olohunfunmi Ismail; Yoncef Bensala; Beglan Baimukhanbetov (DAYAH: Journal of Islamic Education, 2022)
In the world today there is a perennial controversy about teaching sexual education among adolescents, as some have said teaching it is a taboo and some said teaching it will be beneficial to adolescents. Consequently, this causes a dilemma and confusion in the mind of some Muslim adolescents. Therefore, it is necessary to solicit information from the experts in the area of Muslim experts in the area, about their awareness of the issue of sexuality and their view on it. Hence, this study wishes to explore the appropriate ways and methods of introducing and teaching sexuality education from the Islamic perspective. Based on this, the study embarks on qualitative research where semi structured interviews were conducted on 5 Muslim scholars. The findings from the study reveal that the perception of the Muslim scholars on sex education, is greatly centred on inculcation of sexual purity attitudes, sexual modesty training, understanding limitations that exist between the opposite sexes and preparation for a fulfilling marital life. The present findings are implicated for Islamic curriculum on sexual education especially in this era of social media influx.